Beyond the alpha angle: Alternative measurements for quantifying cam‐type deformities in femoroacetabular impingement. Issue 4 (2nd February 2015) - Ehrmann, Christine; Rosskopf, Andrea B.; Pfirrmann, Christian W.A.; Sutter, Reto
<x xml:space="preserve">Abstract</x> Purpose To assess alternative measurements to the alpha angle as a tool for distinguishing between symptomatic and asymptomatic cam‐type deformities of the femoral head. Materials and Methods Magnetic resonance imaging (MRI) examinations of 106 individuals (age 20–50 years) from a previous study on the alpha angle were analyzed, including 53 femoroacetabular impingement (FAI) patients with cam‐type deformities and 53 age‐/sex‐matched asymptomatic volunteers. On radially reformatted MR images two independent radiologists assessed femoral offset and femoral distance (FD) around the femoral head circumference. Intraclass correlation coefficient (ICC) and receiver operating characteristic (ROC) were obtained. Results The mean offset was smallest in the anterosuperior position for both readers: reader 1 measured 6.2 ± 2.9 mm (standard deviation) in patients and 7.3 ± 1.8 mm in volunteers (P = 0.002, patients vs. volunteers); reader 2 measured 6.1 ± 3.3 mm in patients and 7.1 ± 2.9 mm in volunteers (P = 0.111). The mean FD was highest in the anterosuperior position for reader 1 (patients 3.3 ± 1.4 mm; volunteers 1.7 ± 2.2 mm; P < 0.001) and in the anterior position for reader 2 (patients 3.1 ± 1.7 mm; volunteers 2.0 ± 1.5 mm; P = 0.001). Overall interobserver agreement (ICC) was good (offset 0.657/FD 0.632). ROC analysis for offset measurements showed the largest area under the curve in anterosuperior position for reader 1 (0.666) and in posterosuperior position for reader 2 (0.612). For FD measurements, the area under the curve was largest in anterosuperior position for both readers (0.793/0.798). Conclusion While FD measurements were superior to offset measurements and showed similar results to the alpha angle, neither FD nor offset measurements are a reliable tool for discrimination between FAI patients with cam‐type deformities and asymptomatic volunteers. J. Magn. Reson. Imaging 2015;42:1024–1031.